Penyuluhan Perilaku Hidup Bersih Sehat Dan Pemberian Bantuan Sabun Cuci Tangan (Handsanitizer) Serta Pemeriksaan Hemoglobin Pada Murid Madrasah Ibtidaiyah Swasta Sholihin Tanjung Morawa Deli Serdang - M.F. Situmeang, Suryani; Setiyawati, Dewi; Suparni, Suparni (Jurnal Mitra Prima, 2023)
Clean and Healthy Living Behavior is a reflection of a family lifestyle that always pays attention to and maintains the health of all family members. School-aged children are a critical age group, because at that age a child is vulnerable to health problems. Based on our observations, students at the Solihin Tanjung Morawa Private Madrasah Ibtidaiyah carry out activities during breaks at school, they snack in the canteen around the school without washing their hands first due to a lack of knowledge and limited running water facilities. As an alternative for running water facilities, you can use hand sanitizer. Although the best method is to wash your hands with soap and running water. The Clean and Healthy Living Behavior Extension aims to increase the knowledge and understanding of students at the Solihin Tanjung Morawa Private Madrasah Ibtidaiyah School about clean and healthy living behavior, which will ultimately improve the level of children's health. Sometimes washing your hands becomes difficult because it is not always easy to find water and soap. As an alternative, you can use a hand sanitizer, an antiseptic liquid or gel that can be used anywhere and at any time without having to rinse with water. After carrying out outreach activities at the Sholihin Private Madrasah Ibtidaiyah School on July 25 2023, it can be concluded that: There has been an increase in the knowledge of students at the Sholihin Private Madrasah Ibtidaiyah School regarding clean living and how to wash their hands using hand sanitizer correctly. The condition of the Hemoglobin Levels of students at the Sholihin Private Madrasah Ibtidaiyah School whose scores were below normal was 3% of the 60 students examined.